Sosialisasi Obat Keluarga dengan Manfaatan Tanaman Jahe (Zingiber Officinale) sebagai Jamu Instan Kering yang Berkhasiat di Desa Sukasari - Nurazizah; Syura, Ilman; Roihanah; Nirvana; Herdianto; Desniarti; Nurdalillah (Aceh Journal of Community Engagement (AJCE), 2023)
Medicinal plants are plants that are planted and cultivated by the community both in the field and in the yard which are used to fulfill the family's need for medicines. Medicinal plants or TOGA are often referred to as the pharmacy of life. The use of TOGA is utilized empirically because of its many properties and low side effects compared to the use of modern drugs when consuming for a long period of time. This socialization aims to increase the knowledge of the community including the efficacy of ginger, the substances contained in ginger, how to make dried instant ginger, how to serve ginger wedang drinks, and how to select quality ginger that meets Indonesian national standards. From this socialization, the community can also utilize TOGA in an effort to improve health.